Biometric characteristic of the common goldfish Carassius auratus auratus (Linneaus, 1758) in Basra freshwater systems - Habbeb, F.Sh. (Mesopotamian Journal of Marine Sciences, 2022)
About 110 specimens of the goldfish Carassius auratus auratus (Linneaus, 1758) were obtained from the Department of Fisheries and Marine Resources Laboratory College of Agriculture and the Marine Sciences Center, University of Basrah. Morphometric and merestics characteristics were measured, total and standard length ranged between 90-150 mm and between 70-110 mm, respectively. Number of scales in the lateral line ranged from 25 to 27. Number of dorsal branched rays ranged from 14 to 15, gill rakers from 42 to 44. Total vertebrae fin count was 25-27. There were five rays with the branchuiostegal rays.